Implementasi Manajemen Strategi Di SMP Negeri Satap 2 Tellu Limpoe Bone Sulawesi Selatan - Ws Athiyaty Agustina; Agus Tinus; M. Syahri (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This research aims to analyze the implementation of strategic management at SMPN Satap 2 Tellu Limpoe in Bone South Sulawesi. The approach and type of research are qualitative descriptive, with a case study design. The research data was obtained through observation, interviews and documentation studies. Analysis of the data used is data collection, data reduction, data presentation, and conclusion and verification. As for the validity of the data, researchers used the triangulation technique. The results of this study indicate that the implementation of the strategy management SMPN Satap 2 Tellu Limpoe Tellu Limpoe has successfully achieved the goal of the 9-year compulsory education program well and has not succeeded in improving the expected quality of education. The implementation of management strategies implemented consists of four stages. First, the environmental observation stage consists of an internal environment which includes a lack of educators and education staff, incomplete administration, facilities that have not been used optimally, and lack of education funds. The external environment includes the economic background of students and teachers and the location of the school. Second, the strategy formulation stage starts with the creation of a vision and mission. Vision and mission based on observing internal and external environments aim to maintain and develop the existence of schools through several school programs. In the third stage, the implementation of the strategy in realizing the planned program can overcome the drop out rate, overcome the shortage of educators and education personnel, overcome the lack of infrastructure and education funds. Fourth is the evaluation stage which aims to determine the success of the program that has been implemented by the school.Keywords: Implementation, Strategy Management, One Roof School Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi manajemen strategi di SMPN Satap 2 Tellu Limpoe Bone Sulawesi Selatan. Pendekatan dan jenis penelitian ini adalah deskriptif kualitatif, dengan rancangan studi kasus. Data penelitian diperoleh melalui observasi, wawancara dan studi dokumentasi. Analisis data yang digunakan adalah pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan dan verifikasi. Sedangkan untuk keabsahan data, peneliti menggunakan teknik triangulasi. Hasil penelitian ini menunjukkan bahwa implementasi manajemen strategi di SMPN Satap 2 Tellu Limpoe telah berhasil mencapai tujuan program wajib belajar 9 tahun dengan baik dan belum berhasil meningkatkan mutu pendidikan yang diharapkan. Impelemntasi manajemen strategi yang diterapkan terdiri dari empat tahap. Pertama, tahap pengamatan lingkungan terdiri dari lingkungan internalyang meliputi kurangnya pendidik dan tenaga kependidikan, administrasi yang belum lengkap, sarana-prasarana yang belum digunakan secara maksimal, dan dana pendidikan yang kurang.Lingkungan eksternal meliputi latar belakang ekonomi siswa dan guru, dan lokasi sekolah. Kedua, tahap perumusan strategi bermula dari pembuatan visi-misi.Visi-misi yang berdasarkan pada pengamatan lingkungan internal dan eksternalbertujuan untuk mempertahankan dan mengembangkan eksistensi sekolah melalui beberapa program sekolah. Tahap ketiga, implementasi strategi dalam mewujudkan program yang direncankanmampu mengatasi angka drop out, mengatasi kekurangan pendidik dan tenaga kependidikan, mengatasi kekurangan sarana prasarana dan dana pendidikan. Keempat adalah tahap evaluasi yang bertujuan untuk menentukankeberhasilan program yang telah dilaksanakan oleh sekolah.Kata kunci: Implementasi, Manajemen Strategi, Sekolah Satu Atap